Women take care : gender, race and the culture of AIDS - Hogan, Katie, 1960- (Cornell paperbacks., 2001)
Self-sacrificing mothers and forgiving wives, caretaking lesbians, and vigilant maternal surrogates-these "good women" are all familiar figures in the visual and print culture relating to AIDS. In a probing critique of that culture, Katie Hogan demonstrates ways in which literary and popular works use the classic image of the nurturing female to render "queer" AIDS more acceptable, while consigning women to conventional roles and reinforcing the idea that everyone with this disease is somehow suspect. In times of crisis, the figure of the idealized woman who is modest and selfless has repeatedly surfaced in Western culture as a balm and a source of comfort-and as a means of mediating controversial issues. Drawing on examples from journalism, medical discourse, fiction, drama, film, television, and documentaries, Hogan describes how texts on AIDS reproduce this historically entrenched paradigm of sacrifice and care, a paradigm that reinforces biases about race and sexuality. Hogan believes that the growing nostalgia for women's traditional roles has deflected attention away from women's own health needs. Throughout her book, she depicts caretaking as a fundamental human obligation, but one that currently falls primarily to those members of society with the least power. Only by rejecting the stereotype of the "good woman," she says, can Americans begin to view caretaking as the responsibility of the entire society